Enseigner dans le premier degré : système d’épreuves et répertoire de ressources - Thierry Bouchetal (Éducation et Socialisation)
This article focuses on the difficulties of first-degree teachers from the notions of event and resource. This makes it possible to reveal jointly the involvement of the subjects in their work and the elements characterizing the social frameworks and contexts of their professional practice. Our data comes from biographical approaches of primary school teacher during their careers. The analysis reveals professional trajectories shaped by the consequences of a event system articulated to a resource repository, which we can report through modeling. Thus, our results point to five categories of events related to the teaching project and the daily activity to which are added two other categories of events that show strategies for reconfiguring career paths. The resources identified come mainly from the working environment and the different strata of the personal path.